Tác động AI đến hiệu suất bền vững: Vai trò trung gian của năng lực động xanh và đổi mới sáng tạo xanh tại các doanh nghiệp ngành chế biến chế tạo ở Việt Nam - Đinh Thị, Hương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The objective of this research is to examine the influence of artificial intelligence on sustainable performance, specifically through the lens of green dynamic capabilities and green innovation. The findings derived from PLS-SEM analysis, which utilized survey data from 682 managers within manufacturing firms, indicate that AI positively impacts sustainable performance, with green dynamic capabilities and green innovation acting as mediators. Based on these results, this study offers novel theoretical and practical insights into the interplay among artificial intelligence, green innovation, green dynamic capabilities, and sustainable performance. Furthermore, management implications are proposed to provide a foundation for enhancing the sustainable performance of manufacturing enterprises in the near future.